EFEKTIVITAS SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN GURU DI SMP NEGERI TERAWAS KABUPATEN MUSI RAWAS - Yulina, Salvera (Manajer Pendididikan, 2025)
This study aims to analyze the effectiveness of academic supervision conducted by principals in improving the quality of teacher learning at SMP Negeri Terawas, Musi Rawas Regency. The results show that academic supervision planning is carried out systematically and structured, referring to eight main indicators: scheduled supervision, valid and reliable supervision instruments, effective communication, clear policy basis, constructive feedback, follow-up plan, openness, and identification of obstacles. The implementation of academic supervision plays a significant role in encouraging positive changes, including improving teachers' professional attitudes, the quality of lesson planning and implementation, learning evaluation, and a supportive school environment. This supervision also has a direct impact on improving student learning outcomes through adaptive and innovative learning strategies. Despite facing obstacles such as time constraints and schedule flexibility, effective academic supervision is proven to be able to encourage the continuous development of teachers' pedagogical and professional competencies. The implications of this research emphasize the importance of humanistic, collaborative and data-based supervision approaches and the need for integration of academic supervision into school management to create a quality and sustainable education ecosystem.